Water-splitting photocatalyst, and method for manufacturing water-splitting photocatalyst

The photocatalyst addresses the inefficiency of existing water-splitting catalysts by selectively supporting hydrogen generation cocatalysts on specific crystal planes of strontium titanate, improving hydrogen and oxygen production efficiency through optimized crystal plane reactions.

JP2025007197APending Publication Date: 2025-01-17MITSUBISHI MATERIALS CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023108439
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing water-splitting photocatalysts have low efficiency for hydrogen and oxygen production due to uneven decomposition rates across different crystal planes, limiting their ability to efficiently split water and generate hydrogen and oxygen in a short time.

Method used

A water-splitting photocatalyst with a photocatalytic crystal having distinct crystal planes for hydrogen and oxygen production, where a hydrogen generation cocatalyst is selectively supported on the hydrogen-producing crystal plane, utilizing strontium titanate with a chromium oxide layer and rhodium-chromium oxide promoter, and a method for producing this catalyst through selective photoelectrodeposition and mask layer formation.

Benefits of technology

The photocatalyst achieves efficient hydrogen and oxygen production by optimizing the crystal plane-specific reactions, enhancing the hydrogen generation efficiency and overall water decomposition efficiency under light irradiation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025007197000001_ABST
    Figure 2025007197000001_ABST
Patent Text Reader

Abstract

To provide a water-splitting photocatalyst capable of efficiently photodegrading water regardless of a photocatalytic crystal having a different generation rate of hydrogen and oxygen depending on crystal face, and a method for manufacturing a water-splitting photocatalyst.SOLUTION: A water-splitting photocatalyst has: a photocatalytic crystal which includes at least any one of metal oxide, metal nitride and metal sulfide; and a hydrogen-generating co-catalyst including noble metal which is carried by the photocatalytic crystal, and photodegrades water into hydrogen and oxygen by light irradiation, where the photocatalytic crystal has a first crystal face which generates the hydrogen; and a second crystal face which generates the oxygen, and the hydrogen-generating co-catalyst is selectively carried by the first crystal face.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a water-splitting photocatalyst that photodecomposes water into hydrogen and oxygen, and a method for producing the water-splitting photocatalyst. [Background technology]

[0002] In recent years, in order to address energy issues and long-term environmental pollution, the use of hydrogen energy, such as hydrogen vehicles and hydrogen power generation, has been considered in many fields. Traditionally, hydrogen has been produced by steam reforming of fossil fuels. However, producing hydrogen from fossil fuels in this way involves carbon dioxide emissions and the use of fossil fuels, which are limited resources, and this poses challenges from the perspectives of carbon neutrality and the shortage of energy resources.

[0003] To solve these problems, water-splitting photocatalysts have been developed that can directly split water and produce hydrogen when exposed to light such as sunlight. For example, Patent Document 1 discloses a water splitting catalyst in which a metal complex moiety is bound to an organic substance such as an aromatic hydrocarbon group or a fused heterocyclic group having a π-electron conjugated system. Furthermore, Patent Document 2 discloses a water splitting catalyst that contains a precious metal element and a transition metal element other than the precious metal element and is made of a nanoporous material.

[0004] However, the water splitting catalysts disclosed in Patent Documents 1 and 2 have low water splitting efficiency for a given amount of irradiated light, making it difficult to efficiently split water to produce hydrogen and oxygen in a short period of time.

[0005] On the other hand, Patent Document 3 discloses a water splitting catalyst in which a metal oxide promoter is supported on p-type gallium nitride to which a metal atom selected from zinc, magnesium, and beryllium is added, thereby improving water splitting efficiency. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2013-126653 A [Patent Document 2] JP 2023-028320 A [Patent Document 3] JP 2007-125496 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, in Patent Document 3, a single type of metal oxide co-catalyst is supported on the entire gallium nitride support, which poses the problem that water cannot be efficiently split in photocatalyst crystals that have a crystal face where hydrogen is primarily produced and a crystal face where oxygen is primarily produced, as is the case with some water splitting catalysts other than gallium nitride.

[0008] This invention has been made in consideration of the above-mentioned circumstances, and aims to provide a water-splitting photocatalyst that can efficiently photosplit water even in photocatalytic crystals in which the production rates of hydrogen and oxygen differ depending on the crystal face, and a method for producing the water-splitting photocatalyst. [Means for solving the problem]

[0009] In order to solve the above problems, the water-splitting photocatalyst and the method for producing the water-splitting photocatalyst according to one embodiment of the present invention propose the following means. (1) A water-splitting photocatalyst according to aspect 1 of the present invention comprises a photocatalytic crystal containing at least one of a metal oxide, a metal nitride, and a metal sulfide, and a hydrogen generation co-catalyst containing a precious metal supported on the photocatalytic crystal, and is a water-splitting photocatalyst that photosplits water into hydrogen and oxygen by irradiation with light, wherein the photocatalytic crystal has a first crystal face that generates the hydrogen and a second crystal face that generates the oxygen, and the hydrogen generation co-catalyst is selectively supported on the first crystal face.

[0010] (2) A second aspect of the present invention is characterized in that, in the water-splitting photocatalyst of the first aspect, the photocatalyst crystal is an octahedron having a perovskite structure, and the first crystal face is {100}.

[0011] (3) A third aspect of the present invention is characterized in that, in the water splitting photocatalyst of the second aspect, the photocatalyst crystals are strontium titanate.

[0012] (4) A fourth aspect of the present invention is characterized in that in the water splitting photocatalyst of the second or third aspect, a chromium oxide layer is formed on the first crystal face.

[0013] (5) A fifth aspect of the present invention is characterized in that, in the water splitting photocatalyst of any one of the second to fourth aspects, the hydrogen generation promoter is rhodium-chromium oxide.

[0014] (6) A method for producing a water-splitting photocatalyst of aspect 6 of the present invention is the method for producing a water-splitting photocatalyst of aspect 5, characterized in that it comprises the steps of: a chromium oxide layer formation step of adding chromate to a dispersion liquid in which strontium titanate is dispersed, and then irradiating with light to selectively photoelectrodeposit a chromium oxide layer on the first crystal face; a mask layer formation step of adding alcohol to selectively form a mask layer containing alcohol on the second crystal face; a precursor adsorption step of adding a precursor containing a rhodium complex to selectively adsorb the precursor onto the chromium oxide layer on the first crystal face; and a hydrogen generation promoter generation step of heating the strontium titanate on which the precursor is adsorbed to thermally oxidize the chromium contained in the chromium oxide layer and the rhodium contained in the precursor, thereby forming the hydrogen generation promoter made of rhodium-chromium oxide on the first crystal face.

[0015] (7) A seventh aspect of the present invention is characterized in that, in the method for producing a water-splitting photocatalyst of Aspect 6, the precursor is produced by adding an amino acid peptide to an aqueous solution of a rhodium salt and then adding a reducing agent.

[0016] (8) An eighth aspect of the present invention is characterized in that in the method for producing a water-splitting photocatalyst of the sixth or seventh aspect, the pH in the precursor adsorption step is set to 10.0 or less.

[0017] (9) A ninth aspect of the present invention is characterized in that, in the method for producing a water-splitting photocatalyst according to any one of aspects six to eight, the thermal oxidation temperature in the hydrogen generation co-catalyst production process is in the range of 250°C or higher and 350°C or lower.

[0018] (10) A tenth aspect of the present invention is characterized in that in the method for producing a water-splitting photocatalyst according to any one of the sixth to ninth aspects, the alcohol is ethylene glycol. Effect of the Invention

[0019] According to the present invention, it is possible to provide a water-splitting photocatalyst that can efficiently photosplit water even in a photocatalytic crystal in which the production rates of hydrogen and oxygen differ depending on the crystal face, and a method for producing the water-splitting photocatalyst. [Brief description of the drawings]

[0020] [Figure 1] 1 is a schematic diagram showing a water-splitting photocatalyst according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a cross-sectional view of the water-splitting photocatalyst of FIG. 1. [Diagram 3] 1 is a schematic diagram showing the energies of a first crystal face and a second crystal face F2 of strontium titanate. FIG. [Figure 4] 1 is a flow chart showing a step-by-step method for producing a water-splitting photocatalyst according to one embodiment of the present invention. [Diagram 5] 1 is a graph showing the relationship between the pH of a dispersion and the stability of a rhodium complex. [Figure 6] 1 is an image showing STEM-EDS mapping of the first crystal face (100) of a water splitting photocatalyst. [Figure 7] 1 is an image showing STEM-EDS mapping of the second crystal face (110) of a water splitting photocatalyst. [Figure 8]1 is a graph showing the relationship between the concentration of rhodium supported on a first crystal face of a water-splitting photocatalyst and the hydrogen production efficiency. [Figure 9] 1 is a graph showing the relationship between the concentration of chromium supported on a first crystal face of a water-splitting photocatalyst and the hydrogen production efficiency. [Figure 10] 1 is a graph showing the relationship between the calcination temperature of the photocatalyst crystal having a rhodium complex adsorbed thereon and the hydrogen production efficiency and oxygen production efficiency of the obtained water-splitting photocatalyst. [Figure 11] 1 is a graph showing the relationship between the type of alcohol used in the mask layer and the hydrogen production efficiency and oxygen production efficiency of the water-splitting photocatalyst produced. [Figure 12] 1 is a graph showing the relationship between the amount of ethylene glycol added and the hydrogen production efficiency and oxygen production efficiency of the water-splitting photocatalyst produced. [Figure 13] 1 is a graph showing the relationship between the light irradiation time and the hydrogen production efficiency and oxygen production efficiency of the water-splitting photocatalyst produced. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] Hereinafter, a water-splitting photocatalyst and a method for producing a water-splitting photocatalyst, which are one embodiment of the present invention, will be described. Note that the following embodiment is specifically described to better understand the gist of the invention, and does not limit the present invention unless otherwise specified. In addition, the drawings used in the following description may show the main parts enlarged for convenience in order to make the features of the present invention easier to understand, and the dimensional ratios of each component may not necessarily be the same as the actual ones.

[0022] [Water splitting photocatalyst] Fig. 1 is a schematic diagram showing a water-splitting photocatalyst according to one embodiment of the present invention, and Fig. 2 is a cross-sectional view of the water-splitting photocatalyst of Fig. 1. The water-splitting photocatalyst 10 of this embodiment has a photocatalyst crystal 11 containing at least one of a metal oxide, a metal nitride, and a metal sulfide, and a hydrogen generation promoter 12 containing a precious metal supported on this photocatalyst crystal. In this embodiment, the noble metal refers to eight elements: gold, platinum, silver, palladium, rhodium, iridium, ruthenium, and osmium. Of these, rhodium and gold are particularly preferred.

[0023] The photocatalyst crystal 11 is a catalyst material that splits water into hydrogen and oxygen by irradiating light in the presence of water. Materials that can be used as the photocatalyst crystal 11 of this embodiment may be water splitting photocatalyst crystals having a hydrogen generating crystal surface and an oxygen generating crystal surface, such as strontium titanate, lead titanate, titanium oxide, zinc oxide, copper oxide, tungsten oxide, barium lanthanum titanium oxide, bismuth titanium oxide, sodium bismuth titanium oxide, strontium bismuth titanium oxide, bismuth vanadate, barium tantalum oxynitride, lanthanum tantalum oxynitride, strontium niobium oxynitride, tantalum nitride, potassium tantalate, sodium tantalate, potassium niobium oxide, titanium yttrium oxysulfide, cesium bismuth halide, bismuth oxyhalide, bismuth yttrium oxyhalide, bismuth niobium oxyhalide, silver phosphate, cadmium sulfide, and metal layered double hydroxides.

[0024] In this embodiment, crystals of strontium titanate (SrTiO3) are used as the photocatalyst crystals 11. As shown in FIG. 1, strontium titanate is an octahedral crystal having a perovskite structure.

[0025] As shown in Figure 3, strontium titanate has a first crystal face F1, which is a hydrogen generation crystal face where the hydrogen generation reaction occurs, and a second crystal face F2, which is an oxygen generation crystal face where the oxygen generation reaction occurs, when irradiated with light in the presence of water, due to the difference in energy associated with the charge transfer between the crystal faces.

[0026] In octahedral strontium titanate, the first crystal face F1 is a crystal face represented by {100}, that is, it is composed of six faces, the (100) face and equivalent faces ((-100), (010), (0-10), (001), (00-1)). Due to the difference in energy between the crystal faces, the first crystal faces F1 have a higher transfer efficiency of excited electrons than the second crystal faces F2, so the reaction of generating hydrogen, which is a constituent element of water, proceeds primarily.

[0027] In the case of octahedral strontium titanate, the second crystal face F2 is a crystal face represented by {110}, that is, it is composed of the (110) face and 12 faces equivalent to it. Due to the difference in energy between the crystal faces, the second crystal faces F2 have a lower transfer efficiency of excited holes than the first crystal faces F1, so the reaction of generating oxygen, which is a constituent element of water, proceeds primarily.

[0028] In the photocatalyst crystal 11 of this embodiment, a chromium oxide layer 13 made of chromium (III) oxide (Cr2O3) is formed on the first crystal face F1, which is the hydrogen generation crystal face. Such a chromium oxide layer converts a rhodium complex for forming a hydrogen generation promoter into a rhodium-chromium oxide during the production of a water splitting photocatalyst, which will be described later. The chromium oxide layer 13 may be formed to a predetermined thickness so as to cover the first crystal face F1.

[0029] The hydrogen generation promoter 12 is selectively formed only on the first crystal face F1, which is the hydrogen generation crystal face of the photocatalyst crystal 11. In this embodiment, the hydrogen generation promoter 12 is formed on the first crystal face F1 via a chromium oxide layer 13.

[0030] The material applicable to the hydrogen generation promoter 12 of this embodiment may be a noble metal microcrystal suitable for hydrogen generation, such as a single metal based on gold, platinum, rhodium, ruthenium, palladium, iridium, silver, osmium, or the like, or an alloy thereof. In this embodiment, rhodium-chromium oxide (RhCrOx) is used as the hydrogen generation promoter 12. That is, the hydrogen generation promoter 12 may be supported by dispersing rhodium-chromium oxide microcrystals in an island shape on the chromium oxide layer 13 of the first crystal face F1. The average particle size of the hydrogen generation promoter 12 particles formed on the chromium oxide layer 13 may be, for example, in the range of 100 μm or less.

[0031] According to the water-splitting photocatalyst 10 of this embodiment having the above-mentioned configuration, when the water-splitting photocatalyst 10 is irradiated with light, such as sunlight, in the presence of water, the hydrogen production reaction proceeds primarily on the first crystal face F1 due to the water-splitting action of the strontium titanate crystals that constitute the photocatalyst crystal 11.

[0032] And because the hydrogen generation promoter 12 is selectively supported on this first crystal face F1, the hydrogen generation reaction proceeds more efficiently compared to the case where only the photocatalyst crystal 11 is present. This makes it possible to generate hydrogen from water more efficiently in a short period of time with a constant amount of light.

[0033] It is also preferable to selectively support an oxygen generating promoter on the second crystal face F2, which is the oxygen generating crystal face of the photocatalyst crystal 11. With such a configuration, water can be decomposed into hydrogen and oxygen more efficiently by only irradiating it with light. Water can also be efficiently photodecomposed by combining it with bismuth vanadate, which decomposes water and generates oxygen when irradiated with visible light such as sunlight.

[0034] [Method of manufacturing water splitting photocatalyst] A method for producing the water-splitting photocatalyst of the above-mentioned embodiment will be described. FIG. 4 is a flow chart showing a step-by-step method for producing a water-splitting photocatalyst according to one embodiment of the present invention. When manufacturing the water splitting photocatalyst of this embodiment, first, fine crystalline strontium titanate (photocatalytic crystal) is prepared, and the photocatalytic crystal is put into pure water, and then ultrasonic waves are applied to generate a dispersion liquid in which the photocatalytic crystal is dispersed. In this embodiment, for example, a dispersion liquid is prepared by adding 350 mL of ultrapure water to 250 mg of strontium titanate.

[0035] Then, a chromate, for example, potassium chromate (K2CrO4), is added to the dispersion liquid and dissolved, and then light is irradiated (chromium oxide layer forming step S1). The light to be irradiated may be, for example, white light using a mercury lamp as a light source. In this embodiment, the mercury lamp is irradiated for about 90 minutes.

[0036] By irradiating the light in this way, the chromium ions (Cr 6+ ) is selectively photoelectrodeposited onto the first crystal face {100} of strontium titanate, and a chromium oxide layer (Cr2O3) is selectively formed only on the first crystal face {100}.

[0037] Next, the photocatalytic crystals with the chromium oxide layer formed on the first crystal face are washed and subjected to solid-liquid separation, then placed in pure water and ultrasonically applied to produce a dispersion in which the photocatalytic crystals with the chromium oxide layer formed are dispersed. Then, alcohol is added to this dispersion, and ultrasonic waves are applied to form a mask layer made of alcohol so as to cover the second crystal face {110} of the strontium titanate (mask layer formation step S2).

[0038] Since the alcohol adheres to the second crystal face where the strontium titanate is exposed, but does not adhere to the chromium oxide layer, a mask layer made of alcohol can be selectively formed only on the second crystal face. The alcohol to be added is not particularly limited, but ethylene glycol, pentaerythriol, 1,2 propanediol, etc. can be used. In this embodiment, ethylene glycol (C2H6O2) is used as the alcohol for forming the mask layer.

[0039] Next, an alkaline solution such as sodium hydroxide is dropped into the dispersion liquid in which the photocatalyst crystals with the chromium oxide layer formed on the first crystal face and the second crystal face covered with the mask layer are dispersed, and the pH is adjusted to 10.0 or less. Then, a solution of a precursor containing a rhodium complex is added to the dispersion liquid after the pH adjustment. Then, by irradiating light, the clusters of the rhodium complex are selectively photoadsorbed only on the first crystal face {100} (precursor adsorption step S3). In this embodiment, photoadsorption was performed by irradiating visible light for about 45 minutes using a xenon lamp.

[0040] The precursor solution used in the precursor adsorption step S3 can be obtained, for example, by adding an amino acid peptide, such as glutathione, to an aqueous rhodium chloride solution, and then adding a reducing agent, such as sodium borohydride (NaBH4), followed by stirring and filtering.

[0041] In this precursor adsorption step S3, the rhodium complex contained in the added precursor solution is selectively photoadsorbed only on the first crystal face on which the chromium oxide layer is formed, and is not adsorbed on the second crystal face {110} masked by the mask layer made of alcohol. This makes it possible to obtain a photocatalyst crystal in which the rhodium complex is selectively adsorbed only on the first crystal face.

[0042] Next, the photocatalyst crystal with the rhodium complex adsorbed only on the first crystal face is heated under reduced pressure at a temperature in the range of 250° C. to 350° C. in a vacuum firing furnace, for example. As a result, the chromium contained in the chromium oxide layer formed only on the first crystal face and the rhodium contained in the rhodium complex are thermally oxidized, and a hydrogen generation promoter made of rhodium-chromium oxide is selectively formed only on the first crystal face (hydrogen generation promoter generation step S4).

[0043] The fired product is then washed and dried to obtain the water-splitting photocatalyst of this embodiment, in which a chromium oxide layer and a hydrogen generation promoter made of rhodium-chromium oxide are selectively formed only on the first crystal face.

[0044] Although the embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope of the invention and its equivalents as described in the claims, as well as in the scope and spirit of the invention. EXAMPLES

[0045] The water-splitting photocatalyst of the present invention was examined. (Verification example 1: pH and rhodium complex stability and adsorption rate in precursor adsorption step S3) We investigated the pH of the dispersion in which the photocatalyst crystals, in which a chromium oxide layer was formed on the first crystal face of the water-splitting photocatalyst and the second crystal face was covered with a mask layer, and the stability and adsorption rate of the rhodium complex when a precursor solution was added. The results are shown in the graph in Figure 5.

[0046] The results shown in FIG. 5 confirm that increasing the pH can suppress hydrophilic interactions, and that the rhodium complex can exist stably up to a pH of about 10.

[0047] (Verification example 2: STEM-EDS mapping of the first crystal face (100) and the second crystal face (110) of the generated water splitting photocatalyst) For the water-splitting photocatalyst produced according to the manufacturing method of the water-splitting photocatalyst of the embodiment described above, STEM-EDS mapping was observed for the first crystal face (100) and the second crystal face (110) of the water-splitting photocatalyst. The results are shown as images in Figure 6 (first crystal face) and Figure 7 (second crystal face), respectively.

[0048] According to the results shown in FIG. 6, fine particles containing rhodium were adsorbed onto the first crystal face (100) of the strontium titanate, and a chromium oxide film was observed underneath. On the other hand, according to the results shown in FIG. 7, neither fine particles containing rhodium nor a chromium oxide film were observed on the second crystal face (110) of strontium titanate.

[0049] From the above results, it was confirmed that in the water splitting photocatalyst of this embodiment, a chromium oxide film and an oxide containing rhodium, which is a hydrogen generation promoter, are selectively formed only on the first crystal face (100) of strontium titanate.

[0050] (Verification Example 3: Relationship between the concentration of rhodium supported on the first crystal face (100) of the generated water splitting photocatalyst and the hydrogen generation efficiency) The relationship between the concentration (mass%) of rhodium supported on the first crystal face (100) of the water-splitting photocatalyst and the hydrogen production efficiency was investigated. The results are shown in the graph in Figure 8. According to the results shown in FIG. 8, it was confirmed that the hydrogen production efficiency (activity) was highest when the rhodium concentration was 0.1 (mass %).

[0051] (Verification Example 4: Relationship between the concentration of chromium supported on the first crystal face (100) of the generated water splitting photocatalyst and the hydrogen generation efficiency) The relationship between the concentration (mass%) of chromium supported on the first crystal face (100) of the water-splitting photocatalyst and the hydrogen production efficiency was investigated. The results are shown in the graph in FIG. According to the results shown in FIG. 9, it was confirmed that the hydrogen production efficiency (activity) was highest when the chromium concentration was 0.2 (mass %).

[0052] (Verification Example 5: Relationship between the calcination temperature in the hydrogen generation promoter generation step S4 and the hydrogen generation efficiency and the oxygen generation efficiency) In the hydrogen production co-catalyst production process, we investigated the relationship between the calcination temperature of the photocatalyst crystals with adsorbed rhodium complexes and the hydrogen production efficiency and oxygen production efficiency of the resulting water-splitting photocatalyst. The results are shown in the graph in Figure 10.

[0053] According to the results shown in FIG. 10, it was confirmed that the hydrogen generation efficiency (activity) and oxygen generation efficiency (activity) were highest when the calcination temperature in the hydrogen generation promoter generation step was set to 300°C.

[0054] (Verification Example 6: Relationship between the type of alcohol in the mask layer formation step S2 and the hydrogen generation efficiency and oxygen generation efficiency of the generated water-splitting photocatalyst) In the mask layer formation process, we investigated the relationship between the type of alcohol used as the mask layer and the hydrogen production efficiency and oxygen production efficiency of the water-splitting photocatalyst produced. The results are shown in the graph in Figure 11.

[0055] According to the results shown in FIG. 11, it was confirmed that when the mask layer was formed using ethylene glycol among ethylene glycol, pentaerythriol, and 1,2-propanediol, a water-splitting photocatalyst with the highest hydrogen production efficiency (activity) and oxygen production efficiency (activity) could be produced.

[0056] (Verification Example 7: Relationship between the amount of ethylene glycol added in the mask layer formation step S2 and the hydrogen generation efficiency and oxygen generation efficiency of the generated water splitting photocatalyst) In the mask layer formation process, we investigated the relationship between the amount of ethylene glycol added to the mask layer and the hydrogen production efficiency and oxygen production efficiency of the water-splitting photocatalyst produced. The results are shown in the graph in Figure 12.

[0057] According to the results shown in FIG. 12, it was confirmed that when the amount of ethylene glycol added was 1.0 g, a water-splitting photocatalyst with the highest hydrogen production efficiency (activity) and oxygen production efficiency (activity) could be produced.

[0058] (Verification Example 8: Relationship between the light irradiation time in the precursor adsorption step S3 and the hydrogen generation efficiency and oxygen generation efficiency of the generated water splitting photocatalyst) In the precursor adsorption step, we investigated the relationship between the time of light irradiation for photoadsorption of the rhodium complex after the precursor solution was added and the hydrogen production efficiency and oxygen production efficiency of the water-splitting photocatalyst that was produced. The results are shown in the graph in Figure 13.

[0059] According to the results shown in FIG. 13, it was confirmed that a water-splitting photocatalyst with the highest hydrogen production efficiency (activity) and oxygen production efficiency (activity) could be produced when the irradiation time was 45 minutes. [Industrial Applicability]

[0060] INDUSTRIAL APPLICABILITY The water-splitting photocatalyst of the present invention contributes to the realization of a hydrogen production plant capable of producing hydrogen at low cost by splitting water only with sunlight without using electric power, and therefore has industrial applicability. [Explanation of symbols]

[0061] 10...Water splitting photocatalyst 11...Photocatalytic crystal 12...Hydrogen generation promoter 13...Chromium oxide layer F1: First crystal face F2…Second crystal plane

Claims

1. A water splitting photocatalyst comprising: a photocatalytic crystal containing at least one of a metal oxide, a metal nitride, and a metal sulfide; and a hydrogen generation promoter containing a precious metal supported on the photocatalytic crystal, the water splitting photocatalyst photodecomposing water into hydrogen and oxygen by irradiation with light, The photocatalytic crystal has a first crystal face that generates the hydrogen and a second crystal face that generates the oxygen, A water splitting photocatalyst, wherein the hydrogen generation promoter is selectively supported on the first crystal face.

2. 2. The water splitting photocatalyst according to claim 1, wherein the photocatalyst crystal is an octahedron having a perovskite structure, and the first crystal face is {100}.

3. 3. The water splitting photocatalyst according to claim 2, wherein the photocatalytic crystal is strontium titanate.

4. 4. The water splitting photocatalyst according to claim 3, wherein a chromium oxide layer is formed on the first crystal face.

5. 5. The water splitting photocatalyst according to claim 4, wherein the hydrogen generation promoter is rhodium-chromium oxide.

6. A method for producing the water splitting photocatalyst according to claim 5, a chromium oxide layer forming step of adding a chromate to a dispersion liquid in which strontium titanate is dispersed, and then irradiating the dispersion liquid with light to selectively photoelectrodeposit a chromium oxide layer onto the first crystal face; a mask layer forming step of adding alcohol to selectively form a mask layer containing alcohol on the second crystal face; a precursor adsorption step of adding a precursor containing a rhodium complex to selectively adsorb the precursor onto the chromium oxide layer on the first crystal face; a hydrogen generation promoter generating step of heating the strontium titanate having the precursor adsorbed thereon to thermally oxidize the chromium contained in the chromium oxide layer and the rhodium contained in the precursor, thereby forming the hydrogen generation promoter made of rhodium-chromium oxide on the first crystal face; A method for producing a water-splitting photocatalyst, comprising:

7. 7. The method for producing a water-splitting photocatalyst according to claim 6, wherein the precursor is produced by adding an amino acid peptide to an aqueous solution of a rhodium salt, and then adding a reducing agent.

8. 7. The method for producing a water splitting photocatalyst according to claim 6, wherein the pH is adjusted to 10.0 or less in the precursor adsorption step.

9. 7. The method for producing a water splitting photocatalyst according to claim 6, wherein the thermal oxidation temperature is set in the range of 250° C. or more and 350° C. or less in the hydrogen generation co-catalyst production step.

10. 7. The method for producing a water splitting photocatalyst according to claim 6, wherein the alcohol is ethylene glycol.

Citation Information

Patent Citations

  • Optical water decomposition catalyst and its manufacturing method

    JP2007125496A

  • Optically functional material, oxidation-reduction photocatalyst, water decomposition photocatalyst, metal complex, and method for production of the metal complex

    JP2013126653A

  • Water decomposition catalyst

    JP2023028320A